THE EUROPEAN MODEL OF SPORT (Fiep Bulletin - online, 2014)
Description of the ‘European sport model’ with, at the bottom, the local sport clubs, structured within the national or regional sport associations ruling and running the different ‘organised’ or competitive sports. These national sport associations are members of the respective international and/or European sport associations or federations. The paper shows how this ‘organised sport’ has ‘adapted’ the very positive educational, health, social, cultural and play functions of physical activity and sport for all practised without any stress in forms adapted to the individual possibilities and aspirations/motivations of every sportsman and woman, without the stress inherent to competition, mainly to high level sport competitions which have other functions, partly less positive.